Western Blotting (WB) Technique Guideline for Separation and Isolation of Protein - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Western blotting is an important technique used in cell and molecular biology. Using the western blot, researchers can identify specific proteins from the complex mixture of proteins extracted from cells. This technique uses three elements to accomplish this task: (1) separation by size, (2) transfer to a solid support, and (3) marking target proteins using appropriate primary and secondary antibodies to visualize. This paper will attempt to explain the techniques and theory behind western blot, and offer several ways to solve the problem